Implementasi Program Double Track Sebagai Upaya Peningkatan Kompetensi Siswa SMA Negeri 1 Dander Kabupaten Bojonegoro - Naililabidhoh Santoso Putri; Ahmad Suprastiyo; Cahya Lukita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The issue of unemployment in Indonesia remains high, especially among graduates of Senior High Schools (SMA) and Vocational High Schools (SMK). Although the number of SMA/SMK graduates has been increasing every year, not all of them can continue their education to higher education institutions. (PT). Data from the Central Statistics Agency (BPS) 2023 shows that the Open Unemployment Rate (TPT) is dominated by middle school graduates, reaching 17.46%. This impacts the low Human Development Index (IPM), which is influenced by two main indicators: Life Expectancy at School (HLS) and Average Length of Schooling. (RLS). In Bojonegoro Regency, these two indicators show improvement, but there are still challenges in creating a quality workforce. To address this, the Double Track Program was introduced in East Java since 2018. Double Track is the term given to schools that offer two educational programs, namely formal education and entrepreneurship skills programs. This program aims to integrate academic education with vocational skills, providing practical skills to students who do not continue their education to higher education. This program is expected to enhance competencies and foster an entrepreneurial spirit among students.At SMAN 1 Dander Bojonegoro Regency, which has implemented this program, students receive training in five skill areas: culinary arts and fashion design. This program helps students prepare to enter the workforce and develop their own businesses after graduation.This research aims to analyze how the implementation of the Double Track Program at SMAN 1 Dander can enhance students' competencies, which ultimately contributes to reducing unemployment and improving the quality of human resources in the region.